2016
DOI: 10.1002/pbc.26192
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children with relapsed or refractory neuroblastoma: A meta‐analysis of ITCC/SIOPEN European phase II clinical trials

Abstract: Background: Few randomized trials have been conducted in children with relapsed/refractory neuroblastoma and data about outcomes including progression-free survival (PFS) in these patients are scarce. Procedure:A meta-analysis of three phase II studies of children with relapsed/refractory neuroblastoma conducted in Europe (temozolomide, topotecan-vincristine-doxorubicin and topotecantemozolomide) was performed. Individual patient data with extended follow-up were collected from the trial databases after public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 19 publications
1
71
0
3
Order By: Relevance
“…The reported 5-year OS rate for patients after the first relapse of neuroblastoma is 20% [94], with outcomes dependent on the time of relapse and the initial patient tumor stage [94][95][96]. A recently published meta-analysis of three phase II clinical trials run through the SIOPEN group in Europe reported median progression free survival rates of 12.5% and 5.7% for patients with refractory and relapsed disease, respectively, while median OS rates were 27.9 months for patients with refractory disease versus 11.0 months for patients with relapsed disease, confirming the poor outcomes in both cohorts of patients [97].…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 87%
“…The reported 5-year OS rate for patients after the first relapse of neuroblastoma is 20% [94], with outcomes dependent on the time of relapse and the initial patient tumor stage [94][95][96]. A recently published meta-analysis of three phase II clinical trials run through the SIOPEN group in Europe reported median progression free survival rates of 12.5% and 5.7% for patients with refractory and relapsed disease, respectively, while median OS rates were 27.9 months for patients with refractory disease versus 11.0 months for patients with relapsed disease, confirming the poor outcomes in both cohorts of patients [97].…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 87%
“…The prognosis of children with recurrences of high‐risk neuroblastoma is dismal . The reported time periods from the observation of first recurrence to the subsequent progression are short (median intervals 58 days, 4.7 months, 6.4 months), and the overall survival proportions have been poor (20% after 4 years, 20% after 5 years, 7% after 10 years).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of children with recurrences of high‐risk neuroblastoma is dismal . The reported time periods from the observation of first recurrence to the subsequent progression are short (median intervals 58 days, 4.7 months, 6.4 months), and the overall survival proportions have been poor (20% after 4 years, 20% after 5 years, 7% after 10 years). Risk factors for an inferior outcome included stage 4, age ≥18 months at first diagnosis, MYCN amplification, loss of heterozygosity of chromosome 11q, shorter time from diagnosis to first recurrence, abdominal primary tumor, bone marrow metastasis at first diagnosis, recurrent disease (vs refractory disease), and increased lactate dehydrogenase blood levels .…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in high‐risk neuroblastoma (HR‐NBL) therapy, long‐term survival for patients with metastatic or high‐risk disease remains less than 40% . Further, patients who experience a relapse of their disease or fail to achieve complete remission have an extremely poor prognosis with 2‐year survival rates of less than 25% . Better understanding of the biology of NBL is critical in identifying new therapeutic targets and improving outcomes for this patient population.…”
Section: Introductionmentioning
confidence: 99%